1990
DOI: 10.2136/sssaj1990.03615995005400060001x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soil Properties on Unsaturated Hydraulic Conductivity Pore‐Interaction Factors

Abstract: The variability of the pore‐interaction factor, ρ, for a microscopic model proposed for predicting unsaturated hydraulic conductivity, K(θ), from soil water‐retention, Ψ(θ), data was examined in relation to soil particle‐size data and indices, bulk density, organic C, parameters for the van Genuchten Ψ(θ) function, an index (W) of total energy of drainage and soil‐series, toposequential, and geographic groupings. The ρ exhibited no trend relationship to any of the soil properties tested. However, a change in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 0 publications
2
31
0
1
Order By: Relevance
“…A number of researchers have found that the parameter L can be negative (e.g., Schuh and Cline 1990;Kosugi 1999;de Vos et al 1999;Schaap and Leij 2000).…”
Section: Resultsmentioning
confidence: 99%
“…A number of researchers have found that the parameter L can be negative (e.g., Schuh and Cline 1990;Kosugi 1999;de Vos et al 1999;Schaap and Leij 2000).…”
Section: Resultsmentioning
confidence: 99%
“…5 by Mualem (1976). Whereas WoÈ sten and van Genuchten (1988) showed that the parameter varies between À16 and more than 2 and the parameter determined by Schuh and Cline (1990) ranged from about À9 to 15, the eect of the parameter value on the scaling result is still unclear.…”
Section: Introductionmentioning
confidence: 97%
“…(2.10), m = 1 -1/n, and l is a pore-connectivity parameter, estimated to be about 0.5 as an average for many soils (Mualem 1976). However, more recent studies (e.g., Schuh and Cline 1990;Yates et al 1992;Schaap and Leij 1998;Zhang et al 2004;Ward et al 2006) suggest that other values of l may represent the hydraulic behavior of many soils equally well or better. In layered soils, saturationdependent anisotropy, which can lead to increased lateral flow in some layers, is best described by a pore connectivity tensor (Zhang et al 2003Raats et al 2004;Ward et al 2006).…”
Section: Hydraulic Conductivitymentioning
confidence: 99%